One example of a random change of time that transforms a generalized diffusion process into an ordinary one - Aryasova, O.V.; Portenko, M.I. (Інститут математики НАН України, 2007)
We propose a random change of time for a class of generalized diffusion processes such that the corresponding stochastic differential equation (with generalized coefficients) is transformed into an ordinary one (its coefficients are some non-generalized functions). It turns out that the latter stochastic differential equation has no property of the (weak) uniqueness of a solution.